Financial Performance Implications of Corporate Sustainable Expenditures in Economic Capital: The case of Listed Manufacturing Firms in Nigeria - Orinya, John Ogbu; Kurfi, Aminu Kado; Kofarmata, Bala Ado (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
Manufacturing firms’ financial performance is anchored on their respective capital expenditures. Extant studies have not conclusively agreed on the implications of respective capital expenditures on the firms’ financial performance. This study sought to contribute to the discourse by examining the implications of expenditures in economic capital on financial performance of listed manufacturing firms in Nigeria. The study is quantitative, combining descriptive and inferential approaches. A sample of 33 firms, with their annual reports from 2008 to 2022, was surveyed. Panel data from the firms’ annual reports were analysed using generalized least squares regression on STATA. Three hypotheses were tested. Results show that firms’ expenditures in economic capital do have important positive implications for financial performance of the manufacturing firms. Expenditures in research and development displayed the highest positive and significant effect, while expenditures in technological innovation and additions to fixed assets showed positive but insignificant effects on the firms’ financial performance. The a-priori expectation that all three components of sustainable expenditures on economic capitals have positive effects on the firms’ financial performance was met. The study concludes that sustainable expenditures in economic capitals are important for improving financial performance of firms. This suggests that listed manufacturing firms in Nigeria strengthen their policy commitment to consistently engage in research and developments, technological innovations and maintenance of a robust asset structure. The study recommends increased expenditures in technological innovation and fixed assets for the manufacturing firms, and suggests that further research seek to clarify the insignificant effects depicted by these expenditures.